Switch - Law, Ingrid 1970- (Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2015)
"Gypsy Beaumont's magical savvy switches to its opposite when she learns that her mean and decidedly non-magical grandma has Alzheimer's and is going to move in with her family"-- Provided by publisher.